Caption Contest (The Biblical archaeology review, 2025)
Thank you to all those who submitted caption entries for our Summer 2025 cartoon (left), based on 2 Samuel 6:14: "David danced before the Lord with all his might." We are pleased to congratulate Beth Vanderbeck of Charleston, South Carolina, who wrote the winning caption, and our runners-up: "You can tell by the way I […]